Transcriptomic and lipidomic profiling in developing seeds of two Brassicaceae species to identify key regulators associated with storage oil synthesis - Aulakh, Karanbir S. (Kansas State University, 2018)
In plants including the members of Brassicaceae family, such as Arabidopsis thaliana and Brassica juncea, seed storage reserves, which include lipids and proteins, accumulate in seeds during development. Triacylglycerols (TAG) are the major storage lipids found in the developing seeds, petals, pollen grains, and fruits of plants. In Arabidopsis seeds, acyl-CoA: diacylglycerol acyltransferase 1 (DGAT1) is the major enzyme contributing to TAG biosynthesis. In Arabidopsis, dgat1-1 mutants retain 60-80% seed TAG content due to the involvement of phospholipid: diacylglycerol acyltransferase (PDAT1) in acyl-CoA independent TAG biosynthesis. My study focuses on the elucidation and functional characterization of novel genes involved in the regulation of the TAG biosynthesis pathway. In developing seeds of the dgat1-1 mutant, altered fatty acid composition was observed with reduced TAG content and increased polar lipid content as compared to wild type. RNA-Seq of developing Arabidopsis seeds was employed to detect differentially expressed genes in dgat1-1. An empirical analysis for differential gene expression revealed a significant number of differentially expressed genes among all developmental stages in dgat1-1. Significant changes in gene expression profile were detected in lipid-related genes such as lipases and desaturases. RT-PCR was used to confirm the differential expression of major lipid-related genes including DGAT1, PDAT, and FAD2. Lipid profiling of T-DNA insertion mutants for differentially expressed genes revealed significant changes in lipid content and composition. Mutations in a member of the α, β-hydrolase family, encoded by gene named PLIP1, resulted in smaller seed and an altered seed oil phenotype. Also, combining the dgat1-1 and plip1-2 mutations resulted in a lethal phenotype, demonstrating the important role of this enzyme in embryo development and TAG biosynthesis. To identify key components in the regulation of storage lipid biosynthesis, correlation analysis using differential transcript abundance and lipid profile during different stages of seed development from dgat1-1 and wild type lines of Arabidopsis was performed. Using clustering analysis with Pearson correlation coefficient and single linkage identified one cluster of genes which included PLIP1, FAD2, FAD3, and PDCT . Similar analysis using combined data from the neutral and polar fractions resulted in clustering of lipids containing polyunsaturated fatty acids. To investigate the reduced seed germination phenotype for mature seeds of dgat1-1 and non-germinating green seed phenotype of dgat1-1 plip1-2 lines, differential expression (DE) analysis for genes involved in hormone metabolism was performed. Upregulation of expression was observed for genes involved in promoting abscisic acid (ABA) response, which led us to specuate the role of altered hormone metabolism in delayed germination of dgat1-1 seeds. Development of allopolyploid Brassica species from its diploid progenitors involves duplication, loss, and reshuffling of genes leading to massive genetic redundancy. It leads to selective expression or newly acquired role for duplicated homeologs. Differential expression (DE) analysis for homoeologous genes from A and B subgenomes of allopolyploid B. juncea implicated in FA synthesis, acyl editing, and TAG biosynthesis and metabolism was performed. Differential expression (DE) analysis identified the transcriptional dominance of A subgenome homoeologs. Identification of these homoeologs will enable their use in breeding programs directed towards improvement of lipid content and composition in seeds.
Keywords: Arabidopsis; Triacylglycerol; DGAT; PDAT; RNA-Seq; Lipid